Adherent - Kim, Chris W. (Conundrum Press, 2023)
The residents of an isolated village in a dreamlike world scavenge for supplies in the surrounding forest, collecting scattered items left over from a long time past. No one strays far from this community, fearing what may lie beyond it. When they find a stack of notebooks by an unknown author, a young villager becomes obsessed with their contents. She sets out on a quest to find the writer. As she ventures into the unknown, she discovers a world both barren and increasingly complex. The closer she gets to her goal, the more she realizes that the encounter she's been seeking probably won't be what she wanted. --back cover.